Recognition of unanchored polyubiquitin by natural and engineered ubiquitin-binding proteins - Scott, Daniel (2016)
The covalent post-translational modification of selected substrates with the ubiquitin protein has emerged as a central regulatory mechanism, governing protein stability, activity and localisation, and accordingly an array of cellular processes. Ubiquitin signalling versatility arises owing to the diverse nature of (poly)ubiquitin modification, with distinct modifications subsequently transduced in a specific manner by ubiquitin-binding domains found in ubiquitin-binding proteins. In recent years the notion that ubiquitin exerts influence solely via the covalent modification of substrates has been challenged, with unanchored, or substrate-free polyubiquitin chains emerging as key regulators of cellular physiology.